A follow-up study of the "Lighthouse" mentalization-based parenting program: mentalization as a mediator of change - Gervinskaitė-Paulaitienė, Lina; Ruggiero, Matthew; Taubner, Svenja; Volkert, Jana; Barkauskiene, Rasa (Clinical child psychology and psychiatry, 2024)
This paper reports follow-up findings for an Mentalization based treatment (MBT) parenting intervention delivered to a community mental health sample. Parents completed the 12-week version of the Lighthouse Parenting Program (LPP) and were evaluated on parenting practices, parent-child relationships, parental mental health indicators, and child problem behaviour levels. We evaluated the extent to which improvements in mentalizing at follow-up mediated changes in parenting, parental adjustment, mental health, and child outcomes. Results included a reduction in parental coercive behaviours and child problems, improved parent-child relationship, and better parental psychological adjustment and mental health. Improvement in self-focused mentalizing were observed. Self-focused mentalizing mediated the changes in most outcomes from baseline to 3-month follow-up. These results provide strong preliminary evidence that the LPP improves parent and child outcomes. This paper presents the findings from a follow-up study that focused on a Mentalization based treatment (MBT) parenting intervention called the Lighthouse Parenting Program (LPP). This program is designed to enhance parents' ability to understand and respond sensitively to their own mental states (self-focused mentalizing) and to those of their children (child-focused mentalizing) and to strengthen parent-child relationships. We invited parents who had been referred for mental health services or whose children had been referred for mental health services to participate in the 12-week version of the LPP. Our study included 101 parents (82 mothers and 19 fathers). Participants were asked to complete study questionnaires about their parenting practices, mentalization, parent-child relationships, parental mental health indicators, and child problem behaviours before starting the program and 3-month after the program. We also examined whether improved mentalization predicted changes in parenting behaviors, parental well-being, and child problems. Results showed that parents were less likely to engage in coercive behaviors with children, their children exhibited fewer behavioral problems. Parent-child relationships improved, and parents reported enhanced emotional well-being and increased confidence in handling parenting tasks. There was also an improvement in self-focused mentalizing, i.e., how parents understood themselves, their thoughts, feelings and behaviors. The improved parental ability to understand their own mind played a significant role in most of the observed changes in parenting and child outcomes from before the program to three months after its completion. These results provide strong initial evidence that the LPP brings benefits to both parents and children.